Curriculum Development Based on Workplace-Oriented Learning to Improve The Competence of Prospective Early Childhood Education Teachers - Halimah, Leli; Mirawati, Mirawati; Silawati, Endah; Hopiani, Ayu (Vidya Karya, 2024)
This study aims to develop a curriculum design based on Workplace-Oriented Learning (WOL) to improve the professional competence of prospective Early Childhood Education (ECE) teachers. The Educational Design Research (EDR) approach was used in the development of this design, through problem identification, curriculum planning, prototype development, and design evaluation. Through needs analysis and careful planning, this curriculum integrates theory with practice in the field. The results showed that the WOL curriculum was designed according to the current needs in the field. Based on the existing needs, the curriculum design is divided into several stages, including career awareness, career exploration, career preparation, and career training, which allow students to understand the tasks and skills needed in the world of work. With collaboration between educational institutions and industry, this curriculum bridges the gap between theory and practice, preparing students to become PAUD teachers who are ready to face the dynamic demands of early childhood education. Thus, the development of WOL-based curriculum design is expected to make a significant contribution to improving the quality of education and learning in early childhood.